Antifungal prophylaxis in liver transplant recipients: one size does not fit all. Issue 4 (2nd August 2016) - Giannella, M.; Bartoletti, M.; Morelli, M.; Cristini, F.; Tedeschi, S.; Campoli, C.; Tumietto, F.; Bertuzzo, V.; Ercolani, G.; Faenza, S.; Pinna, A.D.; Lewis, R.E.; et al.
Abstract: Background: Targeted antifungal prophylaxis against Candida species or against Candida species and Aspergillus species, according to individual patient risk factors (RFs), is recommended by experts. However, recent studies have reported fluconazole is as effective as broader spectrum antifungals for preventing invasive fungal infection (IFI) after liver transplantation (LT). Methods: We performed a retrospective cohort study of all adult patients who underwent LT at our 1420‐bed tertiary teaching hospital, from June 2010 to December 2014, to assess the rate and etiology of IFI within 100 days after LT, to investigate the compliance with targeted prophylaxis, and to analyze risk factors for developing IFI. Results: In total, 303 patients underwent LT. Patients were classified as having low (no RFs), intermediate (1 RF for invasive candidiasis [IC]), and high risk (1 RF for invasive aspergillosis [IA] or ≥2 RFs for IC) for IFI in 20%, 30%, and 50% of cases, respectively. A total of 139 patients received antifungal prophylaxis: 98 with a mold‐active drug and 41 with fluconazole. Overall adherence to targeted prophylaxis was 53%. Nineteen patients (6.3%) developed IFI: 7 IC and 12 IA. Multivariate Cox regression analysis, adjusted for median model for end‐stage liver disease score at LT, stratification risk group, and adherence to targeted prophylaxis, showed that graft dysfunction, renal replacement therapy, and prophylaxis with fluconazole were independent risk factors for IFI. Seven of the 9 patients who received fluconazole prophylaxis and developed IFI were classified as having high risk for IFI, and 6 developed IA. Conclusion: Recommended stratification is accurate for predicting patients at very high risk for IFI, who should receive prophylaxis with a mold‐active drug.